An enhanced control scheme for multifunctional grid connected PV system using fuzzy and predictive direct power control - Boukezata, Boualem; Chaoui, Abdelmadjid; Gaubert, Jean Paul; Boutalbi, Oussama (Bulletin of Electrical Engineering and Informatics, 2024)
This paper presents a combination between a fuzzy logic control (FLC) and a predictive direct power control for multifunctional grid connected photovoltaic (PV) system, to solve the oscillation problem in the DC link voltage of the in-verter caused by the fast irradiation changing. The whole system consists of a PV system which interface a DC-AC inverter, a FLC maximum power point tracking (MPPT) algorithm has been adopted to operate the DC-DC converter at the MPP. The predictive control strategy is applied to the DC-AC inverter with FLC in its voltage control loop to improve the power exchange between the grid and the PV system. Simulation results have been verified through MATLAB/Simulink software for the purpose of giving the effectiveness of the suggested control against existed controllers.